Familial Interstitial Lung Disease - Kropski, Jonathan A. (Seminars in Respiratory and Critical Care Medicine, 2020)
The interstitial lung diseases (ILDs) are a group of progressive disorders characterized by chronic inflammation and/or fibrosis in the lung. While some ILDs can be linked to specific environmental causes (i.e., asbestosis, silicosis), in many individuals, no culprit exposure can be identified; these patients are deemed to have “idiopathic interstitial pneumonia” (IIP). Family history is now recognized as the strongest risk factor for IIP, and IIP cases that run in families comprise a syndrome termed “familial interstitial pneumonia” (FIP). Mutations in more than 10 different genes have been implicated as responsible for disease in FIP families. Diverse ILD clinical phenotypes can be seen within a family, and available evidence suggests underlying genetic risk is the primary determinant of disease outcomes. Together, these FIP studies have provided unique insights into the pathobiology of ILDs, and brought focus on the unique issues that arise in the care of patients with FIP.
Keywords: IPF; pulmonary fibrosis; genetics; telomere; surfactant; alveolar epithelial cells